ANALYSIS OF THE USE OF SOCIAL MEDIA BETWEEN THE YEARS 2012 AND 2013 FOR THE TOP 50 COMPANIES IN THE BRAZILIAN AGRIBUSINESS - Garzon, Karen Gimenez; Machado, JOÃO Guilherme de Camargo Ferraz (Revista Brasileira de Engenharia de Biossistemas, 2014)
The aim of this research was to analyze the use of social media by companies in the agribusiness sector in Brazil. More specifically, it was sought to classify companies as to the purpose of use and the content posted by these media, comparing them within the same industry. The top 50 companies ranked by Guia Exame Biggest and Best in 2010 and 2011, in the 'Agribusiness' category, were analyzed, allowing comparison of the results. The research used the technique of content analysis, through observation and interpretation of the posts made during 30 consecutive days. For this analysis, categories were created in order to facilitate the classification of the content posted. The results showed a significant increase in the use of Facebook in 2013, while the number of tweets has remained virtually the same. In both cases, the most frequent posting category was 'information', with 34% and 37% of posts, respectively. It was concluded that companies in the agribusiness sector continue using some social media as a communication channel, despite the 109% increase from one year to another.